PENAMBAHAN PROGRAM INTERLOCK DARI SENSOR VIBRASI KE DISTRIBUTED CONTROL SYSTEM CEMENT MILL TUBAN PLANT SEBAGAI SAFETY DEVICE - Iqbal, Aditya; Nurahmawati, Ardika (Universitas Muhammadiyah Surabaya, 2025)
Cement Mill is the place where the final grinding process of cement. Cement Mill at Tuban Factory uses the type of Vertical Roller Cement Mill which is a product from Loesche. One important parameter to note is vibration. High vibrational speeds can damage equipment so it must be limited referring to the manual book from Loesche, which must not exceed 16 mm / s. Therefore, it is necessary to add a pruftechnik vibration sensor program to the Distributed Control System (DCS) cement mill as a safety device. Then after conducting literature studies, continued with concept design and program creation in ABB Control Builder M software using computers for Engineering in factories using function block diagram (FBD) programming language. The result of the program is an additional safety device for cement mills in the form of an interlock system that automatically turns off the cement mill motor drive when the vibration speed value is read beyond 16 mm / s. Apart from being a safety device, the addition of this program also produces real-time monitoring system facilities In the form of an indication of vibration speed along with a graph that can be accessed online, making it easier for operators to find out the vibration value without having to check in the area. Keywords : Cement Mill, DCS, Vibration Sensor, Safety Device